Resiliensi UMKM kuliner tradisional berbasis budaya dalam menghadapi modernisasi: Studi mixed methods pada pedagang pisang epe di Pantai Losari - Muhammad Ilman; Andi Majdah M. Zain; Helda Ibrahim; Awaluddin Yunus (Journal of Agribusiness Science and Rural Development, 2026)
This study aims to analyze the resilience of pisang epe vendors in sustaining their businesses amid modernization in the Pantai Losari area. Previous studies have predominantly emphasized economic aspects in examining MSME resilience, while the integration of cultural and social dimensions remains limited. Therefore, this study addresses this gap by providing a more comprehensive analysis of resilience. The study employs a mixed methods approach, combining qualitative data from in-depth interviews and quantitative data from 152 respondents. The analysis includes validity and reliability tests, as well as multiple linear regression to examine the influence of product quality, price, and service on customer satisfaction and purchase intention. The results indicate that all research instruments are valid and reliable. Empirically, product quality, price, and service have a positive effect on customer satisfaction, with product quality as the most dominant factor. The authenticity of taste serves as the primary competitive advantage in shaping consumers’ perceived value, while price stability creates a perception of fairness, and socially based service strengthens customer loyalty. However, the utilization of digital technology remains limited, indicating that the existing resilience pattern is still traditionally adaptive strong in cultural and social aspects but not yet optimal in digital adoption. The novelty of this study lies in integrating economic, social, and cultural aspects to explain the resilience of traditional culinary MSMEs. This study concludes that business resilience is not solely determined by economic capability but is also influenced by cultural identity and social capital. The findings highlight the importance of strengthening digitalization without undermining traditional values as a strategy for sustaining business competitiveness in the modern era.